The Effectiveness of Grammarly to Promote Student’s English Grammar Competence: A Case Study - Jonathan Tanihardjo; Jovianto Jovianto (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Feedback is of importance in language for language learners, since it is useful to evaluate the learners’ ability and performance when using the target language. Nowadays, with the development of technology, learners have begun to make use of educational applications, like Grammarly to help them review the grammar, spelling, punctuation, and suggest replacement for the identified errors in the English texts. The primary data collected for this study are the results of the student’s grammar test, which test items were taken from the feedback generated by Grammarly. Nugroho (2021) states that feedback on students’ errors is crucial in the learning process, so that students can learn from their mistakes and avoid repeating the same mistakes in the future. The results in this study show that the student managed to correctly identify most of the grammatical errors he previously made in his thesis. The findings show the number of incorrect numbers decreased quite significantly to 11 out of 35 which fell into 6 subcategories with the determiner as the most problematic grammatical error.